A Prospective Cross-Sectional Study on Drug Adherence, Prescription Patterns, Associated Comorbidities and Quality of Life in Patients with Sub-clinical Thyroid Disorders - Nawaz, Syed Aamer; Lavanya, Kota; Bhavitha, Akula; Prasad, Kavya; R, Rathnashree; Khan, Shura (Indian Journal of Pharmacy Practice)
Aim: The evident rise in prevalence of Thyroid disorders in India emphasizes on patient care to be addressed with few challenges like failure to monitor disease condition, poor medication adherence and low frequency of follow-up visits with the physician. Objectives: Objective of this study is to assess the thyroid function and quality of life in patients with subclinical thyroid disorders. Materials and Methods: A cross-sectional study was conducted which comprised of 142 patients with subclinical thyroid disorders and were assessed for their prescription patterns, medication adherence, quality of life and other risk factors using case report form and other standardized scales like Thypro scale and Morisky medication adherence scale. Results: Patients with comorbidities like hypertension, diabetes mellitus, renal disorders and cardiovascular were found to be high and few patients even complained of sleep disorders, hair loss/alopecia and arthritis. Among these, incidence of renal diseases was found to be high in patients with subclinical thyroid disorders. Prescription pattern showed majority of patients with subclinical hypothyroid were prescribed levothyroxine 25mcg and carbimazole10mg for patients with subclinical hyperthyroid. Conclusion: Patients having high medication adherence showed good quality of life and those with poor adherence to medications showed poor quality of life which shows significant relationship between the medication adherence and quality of life.
Keywords: Comorbidities; Medication adherence; Prescription patterns; quality of life; Subclinical thyroid disorders